TRABALHADORES QUE ESTUDAM:TERRITÓRIOS, TRABALHO E ITINERÁRIOS DE APRENDIZAGEM DE ESTUDANTES DA EJA - Andrade, Adriana Kemerich de (2023)
This research aimed to contribute to the recognition of students, of Youth and Adult Education (EJA), as workers. For this, the objective was to identify the learning itineraries of workers who study in the EJA, who attend a school in Santa Maria, RS. From the collected data, categories were elaborated to analyze the results obtained through the Content Analysis method, by Bardin (2006), since the research is qualitative and has as its epistemological foundation the theoretical framework systematized by this author. Data collection was done through questionnaires and focus groups. To compose the sample, students enrolled in the nocturnal EJA modality, frequent, who were willing to answer the questionnaire and expressed interest in participating in the focus group were considered. Eleven students participated in the survey, all answered the questionnaire and 7 participated in the questionnaire and the focus group. The final results pointed to the existence of four learning Itineraries: the biographical (life history); Territory, work and school. Paths, such, that are shown to be interconnected. Having the biography as a guide to socio spatiality, which can lead these subjects to a peripheral territory, to informal work and low education, the consequence of which is social and professional exclusion. In addition to these findings, the profile of the young worker was identified, as well as the territorial and work constraints that prevent progress in educational activities in adulthood, but originating in childhood. In the end, it was proposed the construction of a new school path and specific suggestions on the organization of the school in a way that contemplates the reality of the student worker who needs a more flexible structure to reconcile work time with study time.